MAPPING POLITENESS, IMPOLITENESS, AND HUMBLE-BRAGGING: A BIBLIOMETRIC EXPLORATION OF DISCURSIVE (IM)POLITENESS RESEARCH - Abdul Jabar, Nor Fatin; Abu Bakar, Nurul Najwa; Rahmat, Nurhazlini (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This study provides a comprehensive bibliometric analysis of discursive (IM) politeness scholarship by examining the convergence of three areas: politeness, impoliteness, and humble-bragging in contemporary linguistic research. The analysis employs 625 documents obtained from Scopus and Web of Science (2000–2025), utilizing VOSviewer and the Bibliometrix R-package to identify publication trends, conceptual frameworks, notable authors, citation networks, and patterns of keyword co-occurrence. The findings demonstrate a notable increase in research grounded in Brown and Levinson’s politeness theory and Culpeper’s impoliteness framework, alongside an emerging collective focused on digital engagement, self-presentation, and online emotional strategies. Humble-bragging, while still not well-studied, is becoming an important area of research related to facework, identity performance, and mediated communication studies. The mapping shows that humble-bragging is a mixed discourse practice that blurs the lines between politeness and impoliteness by combining self-promotion with planned modesty. This suggests that the way we think about relational activity in digital contexts has changed. This study integrates disparate research from three domains, demonstrating that humble-bragging is not a marginal phenomenon but a substantial element that alters academic perspectives on pragmatic assessment, online social interaction, and the discursive negotiation of authority and identity. The work underscores the imperative to refine politeness and impoliteness models to include multimodal, platform-driven behaviors, while methodologically it validates bibliometrics as a potent tool for delineating evolving pragmatic contexts.